The Development of Long-Term Adverse Health Effects in Oil Spill Cleanup Workers of the Deepwater Horizon Offshore Drilling Rig Disaster - D’Andrea, Mark A.; Reddy, G. Kesava (Frontiers in Public Health, 2018)
Background The purpose of this study was to assess the long-term adverse health effects of the 2010 Deepwater Horizon Gulf oil spill exposure in workers who participated in its cleanup work. Methods Medical charts of both the oil spill exposed and unexposed subjects were reviewed. The changes in the white blood cells, platelets, hemoglobin, hematocrit, blood urea nitrogen, creatinine, alkaline phosphatase (ALP), aspartate amino transferase (AST), alanine amino transferase (ALT) levels, as well as their pulmonary and cardiac functions were evaluated. Results Medical records from 88 subjects (oil spill cleanup workers, n = 44 and unexposed, n = 44) were reviewed during initial and 7 years follow up visits after the disaster occurred. Compared with the unexposed subjects, oil spill exposed subjects had significantly reduced platelet counts (×103/µL) at their initial (254.1 ± 46.7 versus 289.7 ± 63.7, P = 0.000) and follow-up (242.9 ± 55.6 versus 278.4 ± 67.6, P = 0.000) visits compared with the unexposed subjects (254.6 ± 51.9 versus 289.7 ± 63.7, P = 0.008). The hemoglobin and hematocrit levels were increased significantly both at their initial and follow-up visits in the oil spill exposed subjects compared to the unexposed subjects. Similarly, the oil spill exposed subjects had significantly increased ALP, AST, and ALT levels at their initial and follow-up visits compared with those of the unexposed subjects. Illness symptoms that were reported during their initial visit still persisted at their 7-year follow-up visit. Notably, at their 7-year follow-up visit, most of the oil spill exposed subjects had also developed chronic rhinosinusitis and reactive airway dysfunction syndrome as new symptoms that were not reported during their initial visit. Additionally, more abnormalities in pulmonary and cardiac functions were also seen in the oil spill exposed subjects. Conclusion This long-term follow-up study demonstrates that those people involved in the oil spill cleanup operations experiences persistent alterations or worsening of their hematological, hepatic, pulmonary, and cardiac functions. In addition, these subjects experienced prolonged or worsening illness symptoms even 7 years after their exposure to the oil spill.